On the complex relationship between resilience and hair cortisol levels in adolescence despite parental physical abuse: a fourth wave of resilience research - Kassis, Wassilis; Aksoy, Dilan; Favre, Céline Anne; Arnold, Julia; Gaugler, Stefan; Grafinger, Katharina Elisabeth; Artz, Sibylle; Magnuson, Doug (Frontiers in Psychiatry, 2024)
To understand family's role in adolescents' mental health development and the connection to neurodevelopmental disorders related to experienced parental physical abuse, we first explored resilience pathways longitudinally and secondly, connected the identified patterns to adolescents' hair cortisol levels that are rooted in the hypothalamic-pituitary-adrenal axis as the main stress response system and connected brain structure alterations. We analyzed longitudinal questionnaire data for three consecutive high school years (from seventh to ninth grade) and four survey waves from a representative sample of n = 1609 high school students in Switzerland on violence-resilience pathways. Furthermore, we collected students' hair samples from a subsample of n = 229 at survey wave 4. About 30% of the participating adolescents had been physically abused by their parents. Out of the overall sample, we drew a subsample of adolescents with parental abuse experiences (survey wave 1 n = 509; survey wave 2 n = 506; survey wave 3 n = 561; survey wave 4 n = 560). About 20-30% of adolescents who experienced parental physical abuse escaped the family violence cycle and can be called resilient. By applying a person-oriented analytical approach via latent class and transition analysis, we longitudinally identified and compared four distinct resilience patterns. We identified violence resilience as a multidimensional latent construct, which includes hedonic and eudaimonic protective and risk indicators. Because resilience should not solely be operationalized based on the lack of psychopathology, our latent construct included both feeling good (hedonic indicators such as high levels of self-esteem and low levels of depression/anxiety and dissociation) and doing well (eudaimonic indicators such as high levels of self-determination and self-efficacy as well as low levels of aggression toward peers). The present study confirmed that higher cortisol levels significantly relate to the comorbid pattern (internalizing and externalizing symptoms), and further confirmed the presence of lasting alterations in brain structures. In this way, we corroborated the insight that when studying resilience pathways and trajectories of abused adolescents, biological markers such as hair cortisol significantly enhance and deepen the understanding of longitudinal mechanisms of psychological markers (e.g., self-determination, self-esteem, self-efficacy) that are commonly applied in questionnaires.